Glucose load following prolonged fasting increases oxidative stress-linked response in individuals with diabetic complications - Rauchhaupt, Ekaterina von; Rodemer, Claus; Kliemank, Elisabeth; Bulkescher, Ruben; Campos Campos, Marta; Kopf, Stefan; Fleming, Thomas; Herzig, Stephan; Nawroth, Peter Paul; Szendrödi, Julia; Zemva, Johanna; Sulaj, Alba (Diabetes care, 2024)
Prolonged catabolic states in type 2 diabetes (T2D), exacerbated by excess substrate flux and hyperglycemia, can challenge metabolic flexibility and antioxidative capacity. We investigated cellular responses to glucose load after prolonged fasting in T2D.Glucose-tolerant individuals (CON, n = 10) and individuals with T2D with (T2D+, n = 10) and without (T2D−, n = 10) diabetes complications underwent oral glucose tolerance test before and after a 5-day fasting-mimicking diet. Peripheral blood mononuclear cell (PBMC) resistance to ex vivo dicarbonyl methylglyoxal (MG) exposure after glucose load was assessed. Markers of dicarbonyl detoxification, oxidative stress, and mitochondrial biogenesis were analyzed by quantitative PCR, with mitochondrial complex protein expression assessed by Western blotting.T2D+ exhibited decreased PBMC resistance against MG, while T2D− resistance remained unchanged, and CON improved postglucose load and fasting (−19.0% vs. −1.7% vs. 12.6%; all P = 0.017). T2D+ showed increased expression in dicarbonyl detoxification (mRNA glyoxalase-1, all P = 0.039), oxidative stress (mRNA glutathione-disulfide-reductase, all P = 0.006), and mitochondrial complex V protein (all P = 0.004) compared with T2D− and CON postglucose load and fasting. Citrate synthase activity remained unchanged, indicating no change in mitochondrial number. Mitochondrial biogenesis increased in T2D− compared with CON postglucose load and fasting (mRNA HspA9, P = 0.032). T2D−, compared with CON, exhibited increased oxidative stress postfasting, but not postglucose load, with increased mRNA expression in antioxidant defenses (mRNA forkhead box O4, P = 0.036, and glutathione-peroxidase-2, P = 0.034), and compared with T2D+ (glutathione-peroxidase-2, P = 0.04).These findings suggest increased susceptibility to glucose-induced oxidative stress in individuals with diabetes complications after prolonged fasting and might help in diet interventions for diabetes management.